Evolution of Maotai Wine Packaging Design in Maotai Town Guizhou China - Zongshe, Kang; Ghani, Dahlan Bin Abdul (South Asian Journal of Social Sciences and Humanities, 2024)
Packaging design has become a critical tool for marketers and producers in the wine industry. Consumer behavior is influenced by the effectiveness of design and development strategies, and therefore the study focuses on the changes in the packaging design of Maotai wine. This study intends to explore the evolution of Maotai wine packaging design in Maotai Town, Guizhou, China, known as the production site of Maotai wine. To satisfy the objectives of the study, a qualitative study was developed so that researchers could gain an in-depth understanding of the phenomenon. Semi-structured interviews were conducted with designers and marketers in Maotai Town, Guizhou, China. This flexible approach allowed the evaluation of the perceptions of key stakeholders in the design and marketing of Maotai wine can be captured. The findings of the study offer substantial insights and strategies which can be applied to the design of culturally significant products. The findings offer insights into the overall strategy and vision used by Maotai in the packaging and preparation of Maotai wine. This study, therefore, intended to contribute to a broader understanding of the significance of packaging design along with shedding light on the factors that have impacted Maotai wine packaging design over the years, such as innovation, tradition, and consumers.